2020
DOI: 10.1111/jora.12586
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic‐racial Socialization, Perceived Neighborhood Quality, and Psychosocial Adjustment among African American and Caribbean Black Adolescents

Abstract: Ethnic–racial socialization is employed by ethnic minority parents to support their children’s psychosocial adjustment. These socialization messages may be associated differently with psychosocial adjustment for Black youth according to ethnicity and qualities of the neighborhood context. This research examined whether associations between ethnic–racial socialization messages and psychosocial adjustment vary by ethnicity and perceived neighborhood quality in a nationally representative sample of Black adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…For example, as transmitters, parents react to youth's experiences at school, particularly when it comes to discrimination (e.g., Banerjee & Eccles, 2019). Neighborhood factors also influence parents’ ERS messages (e.g., Lambert et al., 2020; Saleem et al., 2016; Witherspoon et al., 2019), so it is likely that both parents and neighborhoods influence the messages that schools provide and how youth interpret and internalize the messages across contexts. Thus, there is an interplay across contexts for the ERS messages youth receive outside and within schools.…”
Section: The School Ers Transmission Modelmentioning
confidence: 99%
“…For example, as transmitters, parents react to youth's experiences at school, particularly when it comes to discrimination (e.g., Banerjee & Eccles, 2019). Neighborhood factors also influence parents’ ERS messages (e.g., Lambert et al., 2020; Saleem et al., 2016; Witherspoon et al., 2019), so it is likely that both parents and neighborhoods influence the messages that schools provide and how youth interpret and internalize the messages across contexts. Thus, there is an interplay across contexts for the ERS messages youth receive outside and within schools.…”
Section: The School Ers Transmission Modelmentioning
confidence: 99%
“…Additionally, Lincoln, Chatters, Taylor, and Jackson (2007) suggested that the association between racism and depression symptoms differed among African American and Caribbean Black samples, which is attributed to immigrant status and parental messages discussing racial barriers. Another study, Lambert, Rose, Saleem, and Caldwell (2021), found that specific racial socialization dimensions were associated with positive coping behaviors among Afro‐Caribbean youth but found no association for African American adolescents. Future research should engage in intentional sampling among Black populations to adequately test ethnic and cultural group differences in the associations explored in this study.…”
Section: Discussionmentioning
confidence: 99%
“…ERS processes influence ethnic identity development, adjustment outcomes, and responses to discrimination experiences across ethnic-racial groups (Ayón et al, 2020 ; Evans et al, 2012 ; Woo et al, 2020 ). How and when ERS is linked to positive or negative outcomes often varies by contextual factors, the type of ERS assessed, and is likely shaped by the unique historical racialized experiences of different groups (Lambert et al, 2021 ; Liu & Lau, 2013 ; Priest et al, 2014 ; Simon, 2021 ). While ERS practices are necessary for the well-being and survival of racial/ethnic minority youth, SPBS may emerge in racially marginalized youth who internalize messages focused on the need to work harder than White youth to overcome structural barriers to success (Lesane-Brown, 2006 ).…”
Section: The Role Of Family Socialization Processesmentioning
confidence: 99%
“…However, there are mixed findings regarding messages that focus on race and mistrust. For example, other studies show that some messages focused on racism and mistrust are associated with adverse adjustment outcomes (Kyere & Huguley, 2020 ; Lambert et al, 2021 ; Liu & Lau, 2013 ).…”
Section: The Role Of Family Socialization Processesmentioning
confidence: 99%